An Ethical Debate in the Philosophy of Information: Is It Possible to Combine or Reconcile Multiple Ethical Theories in a Common Perspective in Artificial Intelligence? - Nesibe Kantar (Artuklu Akademi)

(untitled)
We live in a cyber-universe created by millions of data sets. This universe, where there are almost no time-space constraints, allows people to perform activities in the intercardinal direction in a comfort they could not imagine before. At the same time, this multicultural and global world (infosphere) is a source of ethical challenges. While living in our unique culture, is it possible to share common ethical values in our world, which is becoming more global with each passing day? Or is it getting more and more impossible in this complex cyber universe? This article draws attention to Bynum's Emerging Ethics theory, which carries the umbrella concept that has the potential to unite people around some common values in ethical practices developed for intelligent systems such as artificial intelligence, even if we have different ethical approaches. The main purpose of this article is how, although different approaches they are, theories based on the common nature of human beings can be combined for the same purpose and Thanks to the 'ethical family unity' structure they have created under the ethical umbrella, it is questioned how they will determine the ethical components that can be applied to intelligence systems like AI for the solution of the common problems of the information age.